STRATEGI KOMUNIKASI POLITIK OPINION LEADER DALAM DIFUSI PROGRAM PEMBANGUNAN DAN PENGEMBANGAN LEMBAGA LOKAL DI PEDESAAN (Opinion Leader Political Communication Strategy in Diffusion Development Program and Development of Local Institutions in Rural) - Selly Oktarina; Sarwititi Sarwoprasodjo (Metacommunication, 2018)
ABSTRACT                 Politics has entered almost every level of society in urban and rural areas. Previously, rural people is very taboo with  "politics", but technological advances can be happen. Diffusion of development program, people in rural need  someone who can be trusted about the issue of  development. One of the political actors who have good credibility is the opinion leader in convincing about development program and development of local institution in rural. The aims of this research are to describe 1) public opinion of rural community, 2) opinion leader political communication strategy in diffusion of development program and  3) opinion leader communication strategy in the development of local institutions in rural. This study uses literature review that related to the topic and described in a descriptive. The results of this research indicate that people in rural areas consider that development programs still tend to be political because based on intervention and  interests in others that local institutions are formed still tend to be a formality. The political communication strategy of opinion leader in the diffusion of development program is  1) interactive communication, 2) political communication in propaganda, 3) communication of political awareness. Opinion leader communication strategy in local institution development is 1) conducting campaign of importance local institution, 2) forming and improving image of local institution, 3) keep harmony among stakeholders, 4) improving performance of change agents..Keywords:  interactive, propaganda, campaign, image, stakeholder.  ABSTRAK Politik sudah memasuki hampir setiap lapisan masyarakat dan berbagai isu yang ada baik di perkotaan maupun di pedesaan. Sebelumnya, bagi masyarakat pedesaan masih sangat tabu dengan namanya “politik”, akan tetapi dengan kemajuan teknologi hal ini dapat terjadi. Untuk meyakinkan masyarakat di pedesaan tentu saja membutuhkan seseorang yang dapat dipercaya mengenai isu pembangunan yang sedang berkembang. Salah satu aktor politik yang memiliki kredibilitas baik adalah opinion leader (pemuka pendapat) dalam menyakinkan masyarakat di pedesaan mengenai program pembangunan dan pengembangan lembaga tani di pedesaan..  Penelitian ini bertujuan untuk mendeskripsikan opini publik masyarakat pedesaan, strategi komunikasi  opinion leader dalam difusi  program pembangunan dan strategi komunikasi  opinion leader dalam pengembangan  lembaga tani di pedesaan. Penelitian ini menggunakan studi literatur yang berkaitan dengan topik dan diuraikan secara deskriftip. Hasil penelitian ini menununjukkan bahwa masyarakat di pedesaan menganggap bahwa program pemerintah masih cenderung bersifat politik karena berdasarkan intervensi dan kepentingan serta lembaga tani yang terbentuk masih cenderung bersifat formalitas saja. Strategi komunikasi politik opinion leader dalam difusi program pembangunan adalah dengan melakukan 1) komunikasi interaktif, 2) komunikasi politik berupa propaganda, 3) komunikasi penyadaran politik. Untuk strategi komunikasi opinion leader dalam pengembangan lembaga tani di pedesaan adalah dengan cara 1) melakukan kampanye pentingnya lembaga tani, 2) membangun dan memperbaiki citra lembaga tani, 3) menjaga keharmonisan antar stakeholder terkait, 4) meningkatkan kinerja agen perubahan..Kata Kunci: interaktif, propaganda, kampanye, citra, stakeholder.